2021
DOI: 10.1108/ijrdm-05-2020-0165
|View full text |Cite
|
Sign up to set email alerts
|

Retail store community and its impact on store success

Abstract: PurposeThe purpose of the study was to examine the potential outcomes of consumers' intention to engage retail store community. The research question focused on: what impact will intention to engage retail store community have on store satisfaction, store commitment, shopping enjoyment and store employee trust?Design/methodology/approachSurvey data were collected from a national panel of 232 adult consumers in the USA. The theoretical model and hypotheses were tested using path analysis in AMOS.FindingsThe mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
(65 reference statements)
1
9
0
Order By: Relevance
“…Consumers with a high level of patronage intention towards a shopping mall are more likely to be committed to the mall. A previous study by Peters and Bodkin (2020) was in line with the study, which demonstrated a relationship between store commitment, customer loyalty and purchase intention.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Consumers with a high level of patronage intention towards a shopping mall are more likely to be committed to the mall. A previous study by Peters and Bodkin (2020) was in line with the study, which demonstrated a relationship between store commitment, customer loyalty and purchase intention.…”
Section: Discussionsupporting
confidence: 86%
“…Further, to measure perceived value, items were adapted from the Hanaysha (2018) study, and the items to assess patronage intention were derived from Grewal et al (2003). The items for store commitment were obtained from Peters and Bodkin (2020). These variables were also measured via a reflective scale.…”
Section: Consumer Patronage Intention In Retailmentioning
confidence: 99%
“…Kim and Kim (2008) examined the shopping modes of browsing verses bargain hunting finding that a high (vs. low) level of shopping enjoyment makes consumers more likely to choose both modes of shopping. Peters and Bodkin (2021) investigated shopping enjoyment and its influence of intention to engage with retail store community. The main objective of a SCLD is encouraging consumers to shop in a brick-and-mortar location buy creating enjoyment through experiential and service-oriented aspects to build an emotional connection with consumers.…”
Section: Psychographic Characteristics Influencing Hedonic and Utilit...mentioning
confidence: 99%
“…Lund et al [231] documented how retailers' engagement with the community can enhance their relationships with consumers. Peters and Bodkin [232] showed that community engagement is associated with consumers' trust in store staff, their enjoyment of the shopping experience, sense of satisfaction with individual stores, and sense of commitment to particular stores. Connections to information may not be too far flung.…”
Section: Community As a Platformmentioning
confidence: 99%